Continued dominance of pandemic A(H1N1) 2009 influenza in Victoria, Australia in 2010 - Grant, Kristina; Franklin, Lucinda; Kacmarek, Marlena; Hurt, Aeron; Kostecki, Renata; Kelly, Heath; Fielding, James (Western Pacific Surveillance and Response, 2013)
The 2010 Victorian influenza season was characterized by normal seasonal influenza activity and the dominance of the pandemic A(H1N1) 2009 strain. General Practice Sentinel Surveillance rates peaked at 9.4 ILI cases per 1000 consultations in week 36 for metropolitan practices, and at 10.5 ILI cases per 1000 in the following week for rural practices. Of the 678 ILI cases, 23% were vaccinated, a significantly higher percentage than in previous years. A significantly higher percentage of ILI patients were swabbed in 2010 compared to 2003–2008, but similar to 2009, with a similar percentage being positive for influenza as in previous years. Vaccination rates increased with patient age. Melbourne Medical Deputising Service rates peaked in week 35 at 19.1 ILI cases per 1000 consultations. Of the 1914 cases of influenza notified to the Department of Health, Victoria, 1812 (95%) were influenza A infections - 1001 (55%) pandemic A(H1N1) 2009, 4 (